Hubungan Jarak Kelahiran dengan Status Gizi Balita - Vita Raraningrum; Reni Sulistyowati (Jurnal Ilmiah Kesehatan Rustida, 2021)
If in less than 2 years the mother is pregnant again, not only will the mother's attention to the child decrease, but the breast milk (ASI) that the child desperately needs will stop coming out. There are many studies that prove that many children suffer from nutritional disorders because their mothers are pregnant again or their new siblings have been born, so that the care for these children is not optimal. Based on observations made on 10 toddlers there are 2 toddlers who have poor nutritional status and 8 toddlers who have good nutrition. After conducting interviews with mothers of under-fives who have malnutrition, they are less than 2 years apart from birth. This study aims to determine the relationship between birth spacing and nutritional status of children under five at posyandu Glenmore Banyuwangi. This type of quantitative research with correlation analytic. The design of this research is cross sectional. The sampling technique used was accidental sampling, the population in this study were all mothers with toddlers totaling 221 people with a sample of 86 people. The results showed that out of 73 toddlers with birth spacing >2 years, 71 people (97.3%) had normal nutritional status and 2 people (2.7%) had obese nutritional status, from 13 toddlers with birth spacing 2 years, 12 people (92.3%) underweight nutritional status and 1 person (7.7%) normal nutritional status. Based on the results of the chi-square test using a computerized system from raw data obtained through a questionnaire, it shows the results with p value = 0.00 then Ho is rejected and Ha is accepted, meaning that there is a relationship between birth spacing and nutritional status of toddlers at Posyandu Glenmore Banyuwangi in 2019/2020.